Prevalence of secondary impairments of adults with cerebral palsy according to gross motor function classification system - Park, Eun-Young (J Phys Ther Sci, 2017)
[Purpose] This study aimed to investigate the prevalence of secondary impairments in adults with cerebral palsy. [Subjects and Methods] The study sample included 52 adults with cerebral palsy who attended a convalescent or rehabilitation center for disabled individuals or a special school for physical disabilities in South Korea. [Results] The univariate analysis showed that the Gross Motor Functional Classification System level was a significant predictor of spondylopathies, general pain, arthropathies, and motor ability loss. The prevalence of these impairments at Gross Motor Functional Classification System level I and II was low compared with the prevalence found at Gross Motor Functional Classification System level III–V. The prevalence of secondary impairments among adults with cerebral palsy at Gross Motor Functional Classification System level III–V was high: loss of motor ability, 42.3%; spondylopathies, 38.4%; general pain, 32.7%; and arthropathies, 28.8%. [Conclusion] In this study, adults with severe cerebral palsy showed a high prevalence of motor ability loss, spondylopathies, arthropathies, and pain. It is necessary to develop intervention programs to prevent secondary impairments in adults with cerebral palsy.